2016
DOI: 10.1097/meg.0000000000000685
|View full text |Cite
|
Sign up to set email alerts
|

Employment status, difficulties at work and quality of life in inflammatory bowel disease patients

Abstract: aObjectives To assess employment status, difficulties at work and sick leave in inflammatory bowel disease (IBD) patients and their relation with sociodemographic and clinical factors, quality of life (QoL), and anxiety and depression. Materials and methods IBD patients attending an IBD outpatients' clinic received self-report questionnaires on employment status, IBD-related difficulties at work and sick leave (Trimbos/iMTA questionnaire for Costs associated with Psychiatric Illness), sociodemographic factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 31 publications
2
44
0
4
Order By: Relevance
“… 21 , 22 These patients may be more likely to experience problems with fatigue, anxiety, depression, deteriorating treatment adherence, and increased work disability. 8 , 21 , 23 A direct consequence will likely be an increased overall use of health care resources. 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 21 , 22 These patients may be more likely to experience problems with fatigue, anxiety, depression, deteriorating treatment adherence, and increased work disability. 8 , 21 , 23 A direct consequence will likely be an increased overall use of health care resources. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Our survey findings of a markedly deleterious effect of IBD on various aspects of professional and academic life are clearly in agreement with data from large surveys, 24 systematic reviews, 10 and other trials. 8 , 9 , 25 For example, in a large European survey in >4,500 IBD patients, most patients reported that their disease had caused absence from work, and 45% commented that IBD had a negative impact on educational performance. 24 Moreover, in a study of IBD patients at a Dutch outpatient clinic, de Boer et al documented that 25% of employed patients were on sick leave, about one quarter were receiving a disability pension, and approximately three quarters had work-related difficulties such as concentration problems and slow work pace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between patient‐reported outcomes is generally high but associated factors should be compared and evaluated in future studies . Several studies have investigated different kinds of patient‐reported outcomes (eg IBDQ, SF36 and FACIT‐F) and factors associated with worse outcomes (eg female gender, smoking and disease activity) . Thus, factors found in this review to be associated with high disability are comparable, although medical treatment (eg biological therapy) and smoking were not associated with worse disability.…”
Section: Discussionmentioning
confidence: 99%
“…They reported difficulties such as concentration problems (72%), having to work at a slower pace than normal (78%), and having to seclude themselves from their colleagues (54%) [8]. A large survey from Japan demonstrated that the percentage of patients who had experienced at least one difficulty at work because of their IBD was 98.3% for ulcerative colitis and 98.8% for Crohn’s disease [9].…”
Section: Introductionmentioning
confidence: 99%